Looking out for myself: Exploring the relationship between conspiracy mentality, perceived personal risk, and COVID‐19 prevention measures. Issue 4 (25th June 2020) - Marinthe, Gaëlle; Brown, Genavee; Delouvée, Sylvain; Jolley, Daniel
Abstract : Objectives: This research examined how conspiracy mentality may affect compliance with preventive health measures necessary to fight the COVID‐19 pandemic, and the underlying motivations to comply. Design and Method: We conducted two cross‐sectional studies (Study 1 N  = 762, Study 2 N  = 229) on a French population, measuring conspiracy mentality, compliance with preventive health measures, and perceived risks related to COVID‐19. We also measured motivations to comply with preventive measures in Study 2. Results: We show that people high in conspiracy mentality are likely to engage in non‐normative prevention behaviours (Study 1), but are less willing to comply with extreme preventive behaviours that are government‐driven (Study 2). However, we demonstrate that a perceived risk to oneself (risk of death) and a motivation to protect oneself can act as a suppressor: Conspiracy mentality is linked with an increase in the perception of risk to oneself, which, in turn, is associated with normative compliance. We also find that perceived risk of death explains the relationship between conspiracy mentality and non‐normative prevention behaviours. Conclusions: Our studies showcase how people high in conspiracy theorizing may (dis)engage with prevention behaviours, but that perceived risk and motivation to protect oneself could increase these individuals' compliance.